Global Entrepreneurship Monitor Caribbean: 2011 Caribbean Regional Report (2012)
The Global Entrepreneurship Monitor (GEM) is conducting the biggest on-going research worldwide in order to study and analyze the relationship that exists between entrepreneurship and the national economic development. This project started in 1999 as an initiative of Babson College and the London School of Economics. At the present time, it is the only comparable data source that exists globally about a wide range of variables associated with the general entrepreneurial activity and specific elements in the different stages that compose the entrepreneurial process.